TMIC-81. INCREASED LEVEL OF IGFBP2 PROMOTES TUMOR METASTASIS IN SHH MEDULLOBLASTOMA. (14th November 2022) - Kunhiraman, Haritha; McSwain, Leon; Shahab, Shubin; Kenney, Anna
Abstract: Medulloblastoma (MB) is the most common pediatric brain malignancy. MB comprises 5 major subgroups known as WNT, SHH p53wt, SHH p53mut, Group 3 and Group 4. Among the four MB subgroups SHH group is the most dominant molecular subgroup in infants and adults. These tumors are proposed to arise from cerebellar granule neuron precursors (CGNPs), whose developmental expansion requires SHH signaling from the neighboring Purkinje neurons. Previous reports suggest that SHH group features a unique tumor microenvironment compared with other MB groups. To better understand how SHH MB cells interact with Tumor Microenvironment, we performed cytokine array analysis of culture media from SHH group Patient Tumor cells, spontaneous SHH MB mouse tumor cells and SHH MB cell lines. Further, confirmed these results using ELISA, Western blot, and immunofluorescence from human SHH MB cell lines, Smo/A1 mouse tumor primary cells and PZp53Med cell lines. In continuation to the observation of IGFBP2 expression in various cell types in single cell analysis, we analyzed the presence of IGFBP2 in astrocytes using Smo/A1 mouse tumor Immunohistochemistry. Our data showed increased levels of IGFBP2 produced by SHH MB cell lines compared to others. We analyzed the role of IGFBP2 in SHH MB tumor growth and metastasis. IGFBP2 knock-down stable cell lines showed phenotypic changes including reduced cell proliferation, cell migration and EMT. Further western blot analysis of IGFBP2 KD cells showed reduced expression of EMT markers also reduced the activation of STAT3. Our preliminary in vitro data suggest IGFBP2 exerts it metastasis-promoting role in SHH MB by regulating the expression of EMT marker proteins and matrix remodeling proteins. Further functional studies suggest that in SHH MB, IGFBP2 may regulate a STAT3-mediated EMT program to metastasize. These findings provide a strong rationale for further pursuing how IGFBP2 promotes medulloblastoma tumor cell growth and migration in vivo .